Evaluation of late toxicity of the concomitant treatment of locally advanced breast cancer: 5- and 10-year follow-up - Skołyszewski, Jan; Brandys, Anna; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2004)
The aim of this study is to evaluate early and late toxicity of concomitant treatment in a group of 430 patients with locoregionally advanced breast cancer in stage III B, treated in the Kraków Centre of Oncology in the period between 1980 and 1992. Neoadjuvant chemotherapy was up-front treatment followed by surgery, postoperative radiotherapy, adjuvant chemotherapy and hormonal treatment. Neoadjuvant chemotherapy based on FAC regimen was applied to 350 patients. CMF regimen was administered to 80 patients. Radical surgery was performed after 2-3 cycles of chemotherapy. Halsted procedure was used in 78% of operated women and Patey procedure in the remaining patients. Two hundred and seventy-five women were irradiated sequentially. Among them 250 patients underwent radiotherapy of the postoperative scar as well as regional lymph nodes. The locoregional therapy was followed by systemic treatment for 12 months in the years between 1980 and 1984 and for 6 months since 1985. FAC regimen was given until a cumulative dose of doxorubicin (450 mg/m 2 ) was achieved and in some patients chemotherapy was continued with CMF regimen. Postmenopausal women were treated with tamoxifen in a daily dose of 20 mg for 2 years. Five-year survival was observed in 34.9% of patients among 430 women with breast cancer in stage III B, including 29.5% of patients with disease-free survival. Ten-year survival was observed in 13.9% and 10% of patients, respectively. Toxicity related to neoadjuvant treatment was not significant and was not a reason for treatment discontinuation. The majority of observed toxicity was grade 1 and 2. More intensive toxicity (grade 3) was related to adjuvant chemotherapy. The late toxicity of concomitant treatment was noted in 93 (21.6%) patients. Lymphatic edema of the upper limb was the most common adverse effect of the treatment. Fibrosis of the lung tissue was seen in 14 patients treated with radiotherapy and brachial plexus damage in 4 patients. Toxicity-related death was observed in 3 women during 10 years of follow-up. Cardiomyopathy related to doxorubicin was the cause of death in 2 women and post radiotherapy lung fibrosis in one woman.